Economic Analysis of Automatic Process Control for Peanut Oil Production by Payback Period Method - May Thida Than; Swe, Wunna (The Indonesian Journal of Computer Science, 2025)
This study examined the production method and rate at a peanut oil production industry in Myingyan Township, Mandalay Region. The actual operation time for each machine was collected from this industry. According to the operation process of this industry, 75% of the workers engaged in peanut oil processing used the traditional technologies, which are labor-intensive and time-consuming. This paper presented a study on improving the production rate of peanut oil through the development and implementation of an automated process control system. To control and automate the production process, a programmable logic controller (Siemens S-7 1200) is used by a ladder logic diagram with TIA portal software. The conventional method produced 752 kg of peanut oil for one day, whereas 1127 kg of oil can be achieved by the automatic method. A detailed methodology for economic analysis of peanut oil production, involving the main variables that affect its profitability, was presented and tested by the payback period method. This method refers to the time it takes to recover the initial investment capital for a cloud project.